2016
DOI: 10.1038/eye.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy with subretinal tissue plasminogen activator and ranibizumab for submacular haemorrhages secondary to age-related macular degeneration: retrospective case series of 45 consecutive cases

Abstract: Purpose To assess the efficacy of smallgauge vitrectomy with subretinal recombinant tissue plasminogen activator (rtPA) and ranibizumab for submacular haemorrhages secondary to neovascular age-related macular degeneration (nAMD), and to identify the factors associated with visual outcome. Methods A retrospective case series was performed, including all patients who had small-gauge vitrectomy with subretinal rtPA and ranibizumab for submacular haemorrhages secondary to nAMD. All patients received three consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
(27 reference statements)
6
21
0
Order By: Relevance
“…Visual outcomes in our patients are like those previously reported in several exudative AMD studies,7 8 11 and had greater improvement than in others 9 10. One study by Gonzalez-Lopez et al reported slightly better outcomes with intervention earlier than 8 days, worse outcomes by area of haemorrhage and a similar overall final BCVA to this cohort at roughly 12-month follow-up 12. More than half of our patients gained vision, with 41.7% of patients gaining significant vision of 3 or more lines at 3 months (figure 1A,B).…”
Section: Discussionsupporting
confidence: 87%
“…Visual outcomes in our patients are like those previously reported in several exudative AMD studies,7 8 11 and had greater improvement than in others 9 10. One study by Gonzalez-Lopez et al reported slightly better outcomes with intervention earlier than 8 days, worse outcomes by area of haemorrhage and a similar overall final BCVA to this cohort at roughly 12-month follow-up 12. More than half of our patients gained vision, with 41.7% of patients gaining significant vision of 3 or more lines at 3 months (figure 1A,B).…”
Section: Discussionsupporting
confidence: 87%
“…Another study used subretinal ranibizumab [27]. e mixture consisted of 0.5-0.7 ml of rtPA 125 μg/ml and 0.06 ml of ranibizumab 10 mg/ml for submacular haemorrhages secondary to neovascular age-related macular degeneration [27].…”
Section: Discussionmentioning
confidence: 99%
“…Subretinal injection of anti-VEGFs was reported in several studies for the treatment of submacular haemorrhage due to exudative age-related macular degeneration [26,27]. e subretinal space, by definition, is the space between RPE cells and photoreceptors [28].…”
Section: Introductionmentioning
confidence: 99%
“…Subretinal injection of anti-VEGFs was reported in several studies for the treatment of submacular haemorrhage due to exudative age-related macular degeneration [26, 27].…”
Section: Introductionmentioning
confidence: 99%